Comparative analysis of four types of mesoscale eddies in the Kuroshio-Oyashio extension region - Sun, Wenjin; An, Mengxuan; Liu, Jie; Liu, Jishan; Yang, Jingsong; Tan, Wei; Dong, Changming; Liu, Yu (Frontiers in Marine Science, 2022)
Oceanic mesoscale cyclonic (anticyclonic) eddies usually have cold (warm) cores and counterclockwise (clockwise) flow fields in the Northern Hemisphere. However, “abnormal” cyclonic (anticyclonic) eddies with warm (cold) cores and counterclockwise (clockwise) flow fields have recently been identified in the Kuroshio-Oyashio Extension (KOE) region. Here, traditional cyclonic cold-core eddies (CCEs) and anticyclonic warm-core eddies (AWEs) are termed normal eddies, and cyclonic warm-core eddies (CWEs) and anticyclonic cold-core eddies (ACEs) are called abnormal eddies. Applying a vector geometry-based automatic eddy detection method to the Ocean General Circulation Model for the Earth Simulator reanalysis data (OFES), a three-dimensional eddy dataset is obtained and used to quantify the statistical characteristics of these eddies. Results illustrate that the number of CCEs, AWEs, CWEs, and ACEs accounted for 38.46, 36.15, 13.40, and 11.99%, respectively. In the vertical direction, normal eddies are concentrated in the upper 2,000 m, while abnormal eddies are mainly found in the upper 600 m of the ocean. On seasonal scales, normal eddies are more abundant in winter and spring than in summer and autumn, with the opposite trend found for abnormal eddies. Potential density changes modulated by normal eddies are dominated by eddies-induced temperature anomalies, while salinity anomalies dominate the changes modulated by abnormal eddies. This study expands the types of eddies and enriches their understanding in the KOE region.